(3GdGbJQGM aj Yde CUhd GdfMhs - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s
(3ChdgG (B:s
(3GdMeO ddg GdPj CQTOfG dGHJcGQ gPG GdfeW gPG cJGH ZQjH GdhVY, YLjH GdUfY hbO SejJg HGdGbJQGM aj Yde CUhd GdfMh s
(3BNQgG (B:s
(3Ke SeYJ GdYQH bO fWbJ ajg aOY eG cfJ Ydjg Edi eG ge Ydjg GfJgi BNQ GdcJGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3fSNI QGHYIs
(3JJab aj ChdgG hBNQgG eY GdfSNI GdChdi HGNJdGa aj HYV GdCdaGXs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B301 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B128 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B534s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B30 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B135s
Keywords: (3GdfMhs